2023
DOI: 10.21608/ejhc.2023.285610
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Female Genital Mutilation at Beni-Suef Governorate, Egypt

Abstract: Background: Female genital mutilation/cutting are procedures in which young girls' and women's external genital organs are manipulated, altered, or removed. Female genital mutilation is considered to be a kind of gender discrimination against women and girls. Aim: The present study was carried find out about FGM in Beni-Suef Governorate. Design: Descriptive Cross-sectional study. Setting: Family Health Centers (FHCs) in different Governorates at Beni-Suef. Sample: Convenient sample. Tools: pre-designed structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 21 publications
1
7
2
Order By: Relevance
“…It is similar to the results of EHIS which reported that the highest prevalence of FGM/C was in rural areas [29]. Also comparable to a study done in Beni-Suef, females from rural regions are far more likely to be mutilated than those from urban ones [17].…”
Section: P<0001supporting
confidence: 89%
See 3 more Smart Citations
“…It is similar to the results of EHIS which reported that the highest prevalence of FGM/C was in rural areas [29]. Also comparable to a study done in Beni-Suef, females from rural regions are far more likely to be mutilated than those from urban ones [17].…”
Section: P<0001supporting
confidence: 89%
“…The mean age of FGM/C discovered in this study was equal to that of FGM/C reported among schoolgirls in Beni-Suef which was (12-16) years (Khamis, et al, 2019). On the other hand, it was lower than the mean age FGM/C discovered among Beni-Suef university student [17].…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…In Egypt, although the prevalence of FGM/C among females aged 15-49 declined from 97% in 1985 to 87% in 2015, the prevalence remains high despite governmental efforts [7][8][9][10]. The prevalence of FGM/C among adolescent girls and women has dropped from 94% in 2008 to 88% in 2014 [10][11][12][13][14][15].…”
mentioning
confidence: 99%